044 Endovascular and transcatheter management of coarctation-related aneurysms in adults. (16th May 2012) - Khavandi, A; Hamilton, M; Martin, R; Parry, A; Brooks, M; Baumbach, A; Turner, M
Abstract : Introduction: Aortic coarctation surgery is associated with a late risk of aneurysm formation. This is particularly seen with patch aortoplasty repair. These aneurysms have a high risk of rupture in the long term as they are frequently false aneurysms. Redo surgery carries significant morbidity and mortality. We describe our experience in treating congenital patients with coarctation-related aortic lesions via endovascular stent grafting and complimentary transcatheter techniques. Methods: Between September 2006 and February 2011, 14 patients with congenital lesions had endovascular or transcatheter descending aortic interventions. 13 received stent grafting with the Medtronic Valiant system with two of these receiving associated vascular closure with the Amplatzer Vascular Plug (AVP 2). One patient had aneurysm closure with the combination of an Amplatzer septal occluder device and vascular occlusion coils. Data regarding these cases has been retrospectively analysed and described. Results: Fourteen patients were treated for late aneurysm formation following prior coarctation surgery (Patch aortoplasty n=10, end-to end anastomosis n=2, interrupted arch type with arch or subclavian to descending aortic Dacron bypass n=2; mean interval from index surgery 30 years (range 22–38 years)). Mean age at intervention was 40 (range 26–62 years). Two patients were treated as emergencies with haemoptysis secondary to fistulae and haemodynamic instability. One patient presented with pain and another with hoarse voice. All patients had successful treatments of the lesion without the need for reintervention. Mean follow-up is 24 months (range 2 months to 54 months) with no mortality and no significant endoleak. Four patients had non-life threatening complications (exercise left arm ischaemic symptoms requiring late vascular bypass, infected surgical vascular access site requiring re-operation, wound infection and re-exploration of neck for chyle leak—related to elective subclavian artery bypass and ligation of aneursmal subclavian prior to stent graft). Conclusion: Even in complex lesions, endovascular stent grafting with complimentary transcatheter and hybrid techniques provides an excellent option for congenital patients avoiding the risks of repeat surgery and the recovery from redo thoracotomy. Concern about the long-term performance of these grafts in young people would appear to be the only downside of this therapy.